Effect of Morinaga Leaves (Morinaga Oleifera) on Breast Milk Production in Post Partum Mothers - Nelly Karlinah (Journal of Midwifery and Nursing, 2021)
Fulfillment of the nutritional needs of infants 0-6 months is absolutely obtained through breast milk (ASI) for infants with exclusive breastfeeding. Based on this, efforts to improve nutrition for infants 0-6 months are carried out through improving maternal nutrition before and during exclusive breastfeeding. However, exclusive breastfeeding always fails this is caused by less milk production. One of the plants that can increase breast milk production is Moringa leaves. Moringa leaves contain laktogogum which can stimulate the hormones oxytocin and prolactin. This study aims to determine the effect of Moringa Leaves (Moringa Oleifera) on breast milk production in post partum mothers in Nelly's Independent Midwife Practice (PMB) Working Area of ??Tapung II Public Health Center, Kec. Tapung. The study was conducted from January to April 2021 by giving Moringa leaves to post partum mothers. This type of research is pre experimental with one group pretest posttest designs. The number of samples in this study was 13 post partum mothers with total sampling technique. Statistical test Paired sample T-test obtained p value of 0.000. The results of statistical tests showed that before being given Moringa leaf steeping the mean value was 32.15 times and there was an increase in breast milk production after being given Moringa leaf steeping, the mean value was 71.23 times. So it can be concluded that there is an effect of Moringa leaves on breast milk production in post partum mothers with a mean difference of 39.08. It is hoped that Moringa leaves can be an alternative physiological therapy to increase breast milk production in postpartum mothers.